A handful of shell tools from Chelbacheb Islands (Rock Islands), Palau - Moser, Johannes (Journal of Global Archaeology, 2024)
During the archaeological surveys as part of the project Documentation of monuments threatened by climate change in Palau some shell artefacts and places with deposited Tridacna shells could be discovered and, in some cases, undoubtedly be interpreted as workshops or knapping ateliers for the production of shell tools. Shells from gastropods and bivalves are a suitable raw material which can be transformed to different artefacts. In fact, artefacts -in the sense of tools, like shell adzes/axes, knives, chisels, scrapers, or projectiles- made from shells are often not recognized as such or receive little attention. In the Pacific region, especially on low atolls and coral islands, due to the lack or rarity of suitable raw material like basalt, chert or obsidian, these shell tools are an essential, if not the most important, part of the inventory.